Structural treatments of space in postmodern arts and their representations in the productions of graduate students in the Department of Art Education (Al-Academy, 2025)
The study aimed to identify the structural treatments of space in postmodern arts and their representations in the products of graduate students in the Department of Art Education. To achieve this, the descriptive analytical approach was used by analyzing the students' products and knowing the structural treatments of the space of the visual artwork in postmodern arts , as she identified (5) main axes and (33) secondary axes. The researcher used (statistical means) both Cooper's equation to calculate the stability ratio, and the arithmetic mean to calculate the total. The researcher concluded that the use of color treatments on the space of the visual surface gave it an aesthetic and expressive dimension. The researcher recommended holding seminars that receive experienced artists in the field of art and conducting dialogues about various arts to enrich the students' culture and inform them of what is new in the artistic field.